Potentiodynamic current/potential relations for film formation under OHMIC resistance control - Calandra, Alfredo J. (1974)
Theoretical potentiodynamic current/potential curves for a film formation process under an ohmic resistance control are given. Results are compared with experimental data involving the formation of insoluble parathiocyanogen on platinum and the precipitation of a solid CuCl layer during copper dissolution in aqueous HCl solution.